Penerapan Strategi Pembelajaran Aktif dalam Meningkatkan Motivasi Belajar Aswaja Siswa di Madrasah - Dianis Izzatul Yuanita (Bidayatuna, 2020)
The problem in the field of education is how the teacher can carry out tasks properly, because lately many students still do not understand Aswaja learning. Is this because students are still less active in participating in the learning process or the teacher's way of teaching is monotonous, so that students become apathetic?. From that, the teacher must choose the right method in using active learning strategies that have a lot of learning methods to activate students in learning in class or outside the classroom. In this study, researchers used a qualitative research type, with collection techniques through 1). Interview 2). Observations and 3). Documentation. Furthermore, data analysis was carried out: 1) Analysis during data collection using descriptive analysis, 2) Data validity techniques using triangulation of data sources.The results showed: 1) The application of active learning strategies in increasing the motivation to learn Aswaja in Madrasah Ibtidaiyah Syarifuddin, namely the method of discussion, jigsaw, question and answer. 2) There is a change in students' motivation to learn that can be seen from activeness, joy, from being lazy to being diligent and enthusiastic, even though there are still some students whose motivation does not increase. 3) Supporting factors: the existence of adequate learning facilities and resources, high student interest in learning, enthusiasm, learning time and professionalism of Aswaja teachers in guiding their students. While inhibiting factors include some students who are still reluctant to express their opinions, learning time and student backgrounds that are different.